Amino acid-hydrated zirconium oxide hybrid material as well as preparation method and application thereof

By hybridizing amino acids with hydrated zirconia to form Arg-HZO and Lys-HZO materials, the problem of insufficient utilization of adsorption sites in removing Cr(VI) and phosphate was solved, and significant adsorption enhancement effect and good regeneration performance were achieved.

CN119633762AActive Publication Date: 2025-03-18ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510119947.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-03-18
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The existing hydrated zirconia (HZO) materials have problems such as insufficient utilization of adsorption sites, high cost, and unrecyclable in removing Cr(VI) and phosphate, which limits the performance of their efficient adsorption capabilities.

Method used

By hybridizing arginine (Arg) and lysine (Lys) with hydrated zirconia (HZO) to form an organic-inorganic molecular-grade hybrid material, and the adsorption performance is enhanced by the interaction of carboxyl and hydroxyl groups.

Benefits of technology

The adsorption amounts of Cr(VI) and phosphate by Arg-HZO and Lys-HZO under the same conditions reached 14-15 times and 12-10 times that of blank HZO, respectively, showing significant adsorption enhancement effect, and have good anti-interference ability and cycle regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633762A_ABST
    Figure CN119633762A_ABST
Patent Text Reader

Abstract

The invention discloses an amino acid-hydrated zirconium oxide hybrid material as well as a preparation method and application thereof, and belongs to the field of water treatment. The specific preparation method of the hybrid material comprises the following steps: dissolving amino acid in deionized water, dropwise adding an ammonium zirconium carbonate solution, and stirring at room temperature to obtain a transparent mixed solution; drying the transparent mixed solution at a constant temperature to obtain a white solid, and soaking, washing and filtering to obtain a white precipitate; and drying the white precipitate at constant temperature to obtain a product. The adsorption capacities of the prepared Arg-HZO on Cr (VI) and phosphate are respectively about 14 and 12 times of those of blank HZO, and the adsorption capacities of the Lys-HZO on Cr (VI) and phosphate are also about 15 and 10 times of those of the blank HZO. Even if competitive ions exist in the solution, the Arg-HZO and the Lys-HZO still have excellent adsorption capacity on Cr (VI) and phosphate, and have good anti-interference capacity. The prepared Arg-HZO and Lys-HZO have the advantages of being environmentally friendly, efficient, good in Cr (VI) and phosphate selectivity, high in mechanical stability and the like, and are promising adsorbents for removing Cr (VI) and phosphate in wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water treatment, and specifically relates to an amino acid-hydrated zirconium oxide hybrid material and a preparation method and application thereof. Background Art

[0002] In today's rapidly evolving human society, the industrialization process continues to advance, industrial and agricultural production is booming, and the population is growing steadily. Although these changes have brought convenience to our lives, they have also caused a series of environmental problems, especially Cr(VI) and phosphate pollution. Cr(VI) is a highly toxic heavy metal that remains stable and easily migrates in the environment. It can enter organisms through the food chain and pose a serious threat to human health. Phosphate is an indispensable nutrient for plant growth, but excessive discharge can cause eutrophication of water bodies and affect the survival of other aquatic organisms. In addition, phosphate can also enter the human body through the food chain, causing harm to human health. At present, a variety of technologies have been developed to remove Cr(VI) and phosphate, including biological methods, chemical methods, and adsorption methods. However, biological treatment and chemical precipitation methods have more or less disadvantages, including high production costs, secondary pollution, and high operating conditions. In contrast, adsorption methods are widely used in wastewater treatment due to their flexible preparation and separation, high efficiency, environmental protection, and recyclability.

[0003] Currently, various adsorbent materials have been reported to remove Cr(VI) and phosphate from water, such as biochar, hydrated metal oxides, metal organic frameworks (MOFs), biopolymers, etc. Despite some achievements in the removal of Cr(VI) and phosphate, most of the prepared adsorbents may have some disadvantages that affect their practical use, including high cost, non-recyclability, poor adsorption capacity and low adsorption rate. Therefore, it is necessary to develop an efficient, environmentally friendly and sustainable adsorbent for the removal of Cr(VI) and phosphate.

[0004] Hydrous zirconium oxide (HZO) is an adsorbent material known for its rich hydroxyl functional groups, wide availability, non-toxicity, environmental friendliness, and tolerance to oxidants, acids, and bases. It is able to remove heavy metal ions through ion exchange and coordination complexation, and can selectively adsorb anions such as phosphate and fluoride ions. Therefore, HZO shows great potential in treating Cr(VI) and phosphorus-containing wastewater. However, HZO also has problems such as dense surface, compact internal structure, and poor dispersibility, which limit the effective utilization of its internal adsorption sites and hinder the full utilization of its high adsorption capacity. Therefore, overcoming the limitations of HZO and fully tapping its adsorption potential are key issues that need to be solved urgently. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides an amino acid-hydrated zirconium oxide hybrid material and a preparation method thereof, so that the internal adsorption sites of the hybrid material can be effectively utilized and the hybrid material has a high adsorption capacity for heavy metals and phosphates.

[0006] The present invention is achieved through the following technical solutions.

[0007] The present invention provides a method for preparing an amino acid-hydrated zirconium oxide hybrid material, which specifically comprises the following steps:

[0008] (1) dissolving the amino acid in deionized water, then dropping the ammonium zirconium carbonate solution, and then stirring at room temperature to obtain a transparent mixed solution;

[0009] The amino acid, ammonium zirconium carbonate and deionized water are used in a mass ratio of 1:3.33-20:4-29;

[0010] (2) drying the transparent mixed solution at a constant temperature to obtain a white solid, and then soaking, washing, and filtering the solid to obtain a white precipitate;

[0011] (3) The white precipitate is dried at a constant temperature to obtain the amino acid-hydrated zirconium oxide hybrid material.

[0012] Furthermore, the amino acid in step (1) is arginine or lysine.

[0013] Furthermore, the stirring time in step (1) is 1 h.

[0014] Furthermore, the drying temperature in step (2) is 120° C. and the drying time is 12 h.

[0015] Furthermore, the drying temperature in step (3) is 70° C. and the drying time is 12 h.

[0016] The amino acid-hydrated zirconium oxide hybrid material prepared by the above preparation method.

[0017] The present invention also provides the application of the amino acid-hydrated zirconium oxide hybrid material in the adsorption of Cr(VI) and phosphate.

[0018] In the above application, as an optimization, the amino acid-hydrated zirconium oxide hybrid material has a pH of 2 to 10 in the adsorption of Cr(VI) and phosphate.

[0019] In the above application, as an optimization, the amino acid-hydrated zirconium oxide hybrid material is added in an amount of 0.25 to 3 g / L in the adsorption of Cr(VI) and phosphate.

[0020] In the above application, as an optimization, the amino acid-hydrated zirconium oxide hybrid material has an adsorption temperature of 298 to 318 K in the adsorption of Cr(VI) and phosphate.

[0021] Compared with the prior art, the present invention has the following technical effects:

[0022] 1. The present invention uses arginine (Arg) and lysine (Lys) to hybridize hydrated zirconium oxide (HZO), and obtains Arg-HZO and Lys-HZO organic-inorganic molecular hybrid materials respectively by a simple sol-gel method, which are used to adsorb Cr (VI) and phosphate in aqueous solution. The carboxyl groups on the Arg and Lys chains will interact with the hydroxyl groups on the HZO molecular chain to complete the fusion from molecules to the overall material from bottom to top, thereby achieving fusion and complementarity from structure to performance. The hydrophilic organic fragments introduced by Arg and Lys are expected to form a large number of water channels running through the Arg-HZO and Lys-HZO overall hybrid materials to make full use of the adsorption sites inside and outside HZO. At the same time, the types and quantities of active adsorption sites (hydroxyl, amino and guanidine) are also increased, thereby enhancing the adsorption potential of HZO, Arg and Lys for Cr (VI) and phosphate.

[0023] 2. Under the same reaction conditions, the adsorption capacity of Arg-HZO for Cr(VI) and phosphate is approximately 14 and 12 times that of blank HZO, respectively, and the adsorption capacity of Lys-HZO for Cr(VI) and phosphate is approximately 15 and 10 times that of blank HZO.

[0024] 3. Competitive ion experiments show that even if there are competing ions in the solution, Arg-HZO and Lys-HZO still have excellent adsorption capacity for Cr(VI) and phosphate, and have good anti-interference ability. More importantly, in the fixed bed column experiment, despite the presence of other competing ions in the solution, Arg-HZO and Lys-HZO can still deeply treat a large amount of phosphate-containing wastewater, demonstrating the great potential of these two materials in practical applications.

[0025] 4. Cyclic adsorption experiments show that after multiple cycles of use, Arg-HZO and Lys-HZO still maintain good adsorption performance for Cr(VI) and phosphate.

[0026] 5. The Arg-HZO and Lys-HZO prepared by the present invention have the advantages of environmental friendliness, high efficiency, good selectivity for Cr(VI) and phosphate, and high mechanical stability, and are a promising adsorbent for removing Cr(VI) and phosphate from wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1The figure is the influence of the ratio of Arg to AZC in the hybrid material of the embodiment of the present invention on the adsorption capacity of Cr(VI) and phosphate (wherein, Figure 1 (a) is the effect of Cr(VI) adsorption capacity, Figure 1 (b) Effect of phosphate adsorption capacity).

[0028] Figure 2 This is a characterization diagram of the hybrid material prepared in Example 1 of the present invention (wherein, Figure 2 (a) is the FESEM image of Arg-HZO. Figure 2 (b) is the TEM image. Figure 2 (c) is the HAADF-STEM image. Figure 2 (d) is the EDX element mapping diagram).

[0029] Figure 3 This is the SEM image of HZO of the present invention.

[0030] Figure 4 FTIR spectra of Arg, HZO and Arg-HZO of the present invention.

[0031] Figure 5 It is the XRD analysis diagram of Arg, HZO and Arg-HZO of the present invention.

[0032] Figure 6 It is the thermogravimetric curve diagram of Arg-HZO and HZO of the present invention.

[0033] Figure 7 This is a diagram showing the effect of the initial pH value of the solution of the present invention on the adsorption of Cr(VI) and phosphate by Arg-HZO and HZO.

[0034] Figure 8 This is a graph showing the effect of the dosage of Arg-HZO on the adsorption capacity of Cr(VI) and phosphate in the present invention.

[0035] Fig. 9 This is a graph showing the effect of adsorption time on the adsorption of Cr(VI) and phosphate by Arg-HZO according to the present invention.

[0036] Fig.10 Graph showing the adsorption capacity of Arg-HZO for different Cr(VI) and phosphate concentrations at three different temperatures (298, 308 and 318 K) of the present invention.

[0037] Fig.11 This is a graph showing the cyclic regeneration performance of Arg-HZO of the present invention.

[0038] Fig.12 The effect of competitive ions on the adsorption of phosphate by Arg-HZO is shown in the figure.

[0039] Fig.13This is a fixed bed column experiment diagram of Arg-HZO of the present invention.

[0040] Fig.14 The effect of the ratio of Lys to AZC in the hybrid material of the present invention on the adsorption capacity of Cr(VI) and phosphate is shown in FIG.

[0041] Fig.15 It is the infrared spectra of Lys, HZO and Lys-HZO of the present invention.

[0042] Fig.16 It is the XRD analysis diagram of Lys, HZO and Lys-HZO of the present invention.

[0043] Fig.17 1 is the thermogravimetric curve of HZO and Lys-HZO of the present invention.

[0044] Fig.18 This is a diagram showing the effect of the dosage of Lys-HZO on the adsorption of Cr(VI) and phosphate.

[0045] Fig.19 This is a diagram showing the effect of the initial pH value of the solution of the present invention on the adsorption of Cr(VI) and phosphate by Lys-HZO and HZO.

[0046] Fig. 20 This is a graph showing the effect of the adsorption time on the adsorption of Cr(VI) and phosphate by Lys-HZO of the present invention.

[0047] Fig.21 Graph showing the adsorption capacity of Lys-HZO for different Cr(VI) and phosphate concentrations at three different temperatures (298, 308 and 318 K) according to the present invention.

[0048] Fig. 22 Graph showing the effect of competing ions on the adsorption of Cr(VI) and phosphate by Lys-HZO according to the present invention. DETAILED DESCRIPTION

[0049] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0050] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0051] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0052] Example 1

[0053] Weigh 3.2g of arginine and dissolve it in 20.8g of deionized water, then add it dropwise to 16g of ammonium zirconium carbonate solution under stirring, wherein the mass of fixed AZC is 40% of the total solution, Arg accounts for 20% of the mass of AZC, and stir at room temperature for 1h to obtain a transparent mixed solution. Then, the mixed solution is dried at 120°C in a constant temperature drying oven for 12h, and the obtained white solid is fully soaked and washed with deionized water. Thereafter, it is filtered multiple times with filter paper ≥800nm, and the obtained precipitate is dried at 70°C in a constant temperature drying oven for 12h to obtain Arg-HZO organic-inorganic molecular hybrid material as an adsorbent.

[0054] Example 2

[0055] The difference from Example 1 is that Arg accounts for 5% of the mass of AZC.

[0056] Example 3

[0057] The difference from Example 1 is that Arg accounts for 10% of the mass of AZC.

[0058] Example 4

[0059] The difference from Example 1 is that Arg accounts for 30% of the mass of AZC.

[0060] Comparative Example 1

[0061] The difference from Example 1 is that Arg is not added, and the AZC solution (prepared by slowly dropping 16 g of AZC into 24 g of deionized water) is directly dried in a constant temperature drying oven at 120° C. for 12 h to obtain a control sample of hydrated zirconium oxide (HZO) as an adsorbent.

[0062] Example 5

[0063] Figure 1 (ab) Effect of the ratio of Arg to AZC in the hybrid material on the adsorption capacity of Cr(VI) and phosphate.

[0064] Experimental conditions: Cr(VI) solution: pH=2, C0=150 mg / L, adsorbent dosage=1 g / L, t=12 h, T=25°C; phosphate solution: pH=2, C0=60 mg / L, adsorbent dosage=0.5 g / L, t=12 h, T=25°C.

[0065] It can be seen that the adsorption capacity of Cr(VI) and phosphate increases first and then decreases slowly with the increase of Arg dosage. Therefore, the composite adsorbent prepared with Arg dosage of 20% of the mass of AZC was selected for subsequent experiments and recorded as Arg-HZO.

[0066] The surface morphology of the samples was analyzed by FESEM. Figure 2 (a) shows that Arg-HZO presents a dense stacking structure, which is very different from the particle morphology of HZO of varying sizes ( Figure 3 TEM was used to further characterize the internal morphology of the hybrid material ( Figure 2 (b)), it is observed that there are no HZO nanoparticles in the Arg-HZO hybrid material. HAADF-STEM image ( Figure 2 (c)) also shows that there are no HZO nanoparticles in the hybrid material. Figure 2 (d) is the elemental mapping of Arg-HZO, where the presence of four elements, C, N, O, and Zr, is observed. Among them, C and N elements belong to Arg, while O and Zr elements come from HZO. It is worth noting that the uniform distribution of N and Zr elements indicates that the hybridization of Arg and HZO is uniform.

[0067] FTIR spectroscopy was used to analyze the group changes produced by the hybridization of Arg and HZO. Figure 4 As shown, the peak of C=O is from 1678cm -1 Red shifted to 1631 cm -1 , reflecting the interaction between the carboxyl group in Arg and the hydroxyl group in HZO. FTIR spectral analysis showed that Arg was successfully hybridized with HZO through intermolecular interactions, and HZO retained the original adsorption sites and introduced other functional groups (amino and guanidine groups) that could serve as new active adsorption sites.

[0068] The crystal structure of the hybrid material was understood through the XRD spectra of Arg, HZO and Arg-HZO ( Figure 5 ). Obviously, both Arg-HZO and HZO exist in amorphous phase, which is very different from the crystal structure of Arg. The hybridization of Arg and HZO is uniform and tight, which leads to the destruction of the crystallinity of Arg, and Arg-HZO is an amorphous or crystal-poor hybrid material.

[0069] Figure 6 Thermogravimetric curves of Arg, HZO and Arg-HZO. It can be observed that HZO completely decomposes at about 500°C, while Arg-HZO needs a higher temperature to completely decompose, which indicates that the hybrid material has better thermal stability.

[0070] Example 6

[0071] This example investigates the effect of the initial pH value of the solution on the adsorption of Cr(VI) and phosphate by Arg-HZO and HZO.

[0072] Experimental conditions: Cr(VI) solution: pH = 2-10, C0 = 150 mg / L, adsorbent dosage = 1 g / L, t = 12 h, T = 25 °C; phosphate solution: pH = 2-10, C0 = 60 mg / L, adsorbent dosage = 1 g / L, t = 12 h, T = 25 °C.

[0073] The results are as follows Figure 7 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. It can be seen that the adsorption capacity of Arg-HZO and HZO for Cr(VI) and phosphate reaches the maximum at pH = 2, and then decreases rapidly with the increase of pH value. However, it is worth noting that at any pH value, the adsorption capacity of Arg-HZO for Cr(VI) and phosphate is higher than that of HZO, confirming that Arg-HZO has better adsorption performance.

[0074] Example 7

[0075] This example investigates the effect of the dosage of Arg-HZO on the adsorption of Cr(VI) and phosphate.

[0076] Experimental conditions: Cr(VI) solution: adsorbent dosage = 0.5-2.5 g / L, C0 = 100 mg / L, pH = 2, t = 12 h, T = 25°C; phosphate solution: adsorbent dosage = 0.25-1.25 g / L, C0 = 60 mg / L, pH = 2, t = 12 h, T = 25°C.

[0077] The results are as follows Figure 8 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. With the increase of adsorbent dosage, the adsorption of Cr(VI) and phosphate by Arg-HZO increased significantly. However, when the dosage exceeded a certain value, the adsorption capacity remained almost constant, which was due to the excessive adsorbent causing the overlap of adsorption sites and the decrease in the ratio of Cr(VI) and phosphate to active adsorption sites.

[0078] Example 8

[0079] This example investigates the effect of adsorption time on the adsorption of Cr(VI) and phosphate by Arg-HZO.

[0080] Experimental conditions: Cr(VI) solution: t=0-400min, C0=100mg / L, pH=2, adsorbent dosage=1g / L, T=25℃; phosphate solution: t=0-1000min, C0=40,60mg / L, pH=2, adsorbent dosage=0.5g / L, T=25℃.

[0081] The results are as follows Fig. 9As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. The adsorption rate is very fast in the early stage of adsorption. As the reaction time increases, the adsorption rate gradually slows down until it reaches adsorption equilibrium. This change in adsorption trend can be attributed to: in the early stage of adsorption, there are a large number of available adsorption sites on the adsorbent; in addition, the high concentrations of Cr(VI) and phosphate in the solution at this time result in a large concentration difference at the solid-liquid interface, which is conducive to increasing the adsorption rate of Cr(VI) and phosphate. In the later stage of adsorption, most of the adsorption sites are occupied, resulting in a decrease in effective adsorption sites. In addition, the concentrations of Cr(VI) and phosphate in the solution decrease, causing the adsorption rate to gradually slow down until it reaches adsorption equilibrium.

[0082] Example 9

[0083] This example investigates the adsorption capacity of Arg-HZO for different Cr(VI) and phosphate concentrations at three different temperatures (298, 308, and 318 K).

[0084] Experimental conditions: Cr(VI) solution: T = 298-318K, C0 = 75-200mg / L, pH = 2, adsorbent dosage = 1g / L, t = 10h; phosphate solution: T = 298-318K, C0 = 40-80mg / L, pH = 2, adsorbent dosage = 0.5g / L, t = 16h.

[0085] The results are as follows Fig.10 As shown, (a) is the adsorption diagram of Cr(VI), and (b) is the adsorption diagram of phosphate. It can be seen that the adsorption capacity of Arg-HZO increases with the increase of the initial concentration. At the same time, the adsorption capacity also increases slightly with the increase of temperature, which indicates that the increase of temperature is conducive to adsorption, and the process of Arg-HZO adsorbing Cr(VI) and phosphate is an endothermic reaction.

[0086] Example 10

[0087] Tables 1 and 2 show the comparison of Cr(VI) and phosphate adsorption by other zirconium-based adsorbents and Arg-HZO adsorbent:

[0088] It can be seen that the adsorption amount of Arg-HZO for Cr(VI) and phosphate is higher than that of most zirconium-based adsorbents in the literature, indicating that Arg-HZO has great research value in the removal of Cr(VI) and phosphate.

[0089] The other zirconium-based adsorbents in Table 1 are polypyrrole-modified α-zirconium phosphate nanocomposite (PPy-ZrPO4), zirconia intercalated sodium montmorillonite composite (ZrO2-NaMMT@700), zirconium metal organic framework modified by Nitrosomonas, and zirconium-loaded mesostructured silica nanoparticles (Zr / MSN). Among them, polypyrrole-modified α-zirconium phosphate nanocomposite (PPy-ZrPO4) is from the literature "Materials Chemistry and Physics, 2022, 290:126540", zirconia intercalated sodium montmorillonite composite (ZrO2-NaMMT@700) is from the literature "Journal of Environmental Chemical Engineering, 2021, 9(5):106053", and zirconium metal organic framework modified by Nitrosomonas is from the literature "Chemical Engineering Journal, 2019, 360: 879-889”, zirconium-loaded mesostructured silica nanoparticles (Zr / MSN) are from the literature “Industrial & Engineering Chemistry Research, 2018, 58(2): 704-712”.

[0090] Table 1 Comparison of Cr(VI) removal capacity with other zirconium-based adsorbents

[0091]

[0092] The other zirconium-based adsorbents in Table 2 are zirconium-modified magnesium-aluminum layered double hydroxide (Zr-LDH), La-Zr bimetallic modified magnetic adsorbent (La-Zr@Fe3O4), Fe3O4 / ZrO2 composite material (Fe3O4 / ZrO2), polyethylene glycol-modified alginate-Zr 4+ and PNIPAM interpenetrating network bead adsorbent (PEG-modified PNIPAM / SA-Zr hydrogel bead), among which zirconium-modified magnesium-aluminum layered double hydroxide (Zr-LDH) comes from the literature "Environmental Progress & Sustainable Energy, 2021, 41(2): e13744", La-Zr bimetallic modified magnetic adsorbent (La-Zr@Fe3O4) comes from the literature "Chemical Engineering Journal, 2021, 413: 127530", Fe3O4 / ZrO2 composite material (Fe3O4 / ZrO2) comes from the literature "Chemical Engineering Journal, 2023, 451: 139817", polyethylene glycol-modified alginate-Zr4+ and PNIPAM interpenetrating network bead adsorbent (PEG-modified PNIPAM / SA-Zr hydrogel bead) from the literature "International Journal of Biological Macromolecules, 2019, 126: 1133-1144".

[0093] Table 2 Comparison of phosphate removal ability with other zirconium-based adsorbents

[0094]

[0095] Embodiment 11

[0096] This example investigates the cyclic regeneration performance of Arg-HZO.

[0097] Experimental conditions: Cr(VI) solution: C0=100 mg / L, pH=2, adsorbent dosage=1 g / L, t=10 h, T=25°C, NaOH=0.1 M; phosphate solution: C0=40 mg / L, pH=2, adsorbent dosage=0.5 g / L, t=16 h, T=25°C, NaOH=0.1 M.

[0098] The results are as follows Fig.11 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. It can be seen from the figure that after 5 cycles of adsorption tests, Arg-HZO still has good adsorption performance for Cr(VI) and phosphate. Therefore, Arg-HZO has good regeneration and reusability and is an efficient adsorbent for treating Cr(VI) and phosphate ions.

[0099] Example 12

[0100] This example investigates the effect of competing ions on the adsorption of phosphate by Arg-HZO.

[0101] Experimental conditions: C0 = 40 mg / L, pH = 2, adsorbent dosage = 0.5 g / L, t = 16 h, T = 25 ° C, Cl - 、SO4 2- and NO3 - =0.01-0.1mol / L.

[0102] The results are as follows Fig.12 As shown. - and NO3 - The presence of SO4 has a negligible effect on the phosphate adsorption capacity, while 2- This may be due to the different hydration radius and negative charge of the ions, SO42- Because of the similar hydration radius with phosphate ions, they compete for adsorption sites. Therefore, compared with monovalent anions, divalent anions will reduce the adsorption performance of Arg-HZO. However, despite this, Arg-HZO still has good anti-interference ability and has broad development prospects in the adsorption of phosphate.

[0103] Example 13

[0104] This example explores the fixed bed column experiment of Arg-HZO.

[0105] Experimental conditions: adsorbent weight = 4.7 g, bed height = 3.3 cm, bed volume = 5.08 mL, phosphate concentration = 5 mg / L, Cl - =6mg / L, NO3 - =1mg / L, SO4 2- =10mg / L, pH=2, flow rate=10BV / h exhaustion point (C t / C0)=90%.

[0106] The results are as follows Fig.13 As shown. It can be seen that despite the presence of coexisting ions (Cl - 、NO3 - and SO4 2- ), Arg-HZO can effectively treat 15.30L of phosphate wastewater, keeping its effluent concentration below 0.3mg / L. At the same time, when Arg-HZO reaches the exhaustion point, the maximum treatment capacity of synthetic wastewater can reach 71.40L. In summary, Arg-HZO has excellent ability to deeply treat phosphate-containing wastewater and is an adsorption material with broad practical application potential.

[0107] Embodiment 14

[0108] Weigh 1.75g ​​of lysine (Lys) in 68.25g of deionized water and stir at room temperature. After Lys is completely dissolved, slowly add 30g of ammonium zirconium carbonate (AZC) solution while stirring continuously, and then stir at room temperature for 1h. Then transfer the mixed solution to a petri dish and dry it in a constant temperature drying oven at 120°C for 12h, then soak and wash the dried block sample with deionized water several times. Then filter the soaked sample repeatedly with filter paper ≥800nm ​​for more than 3 times, and finally put the obtained powder into a constant temperature drying oven at 70°C and dry it for 12h. In this way, Lys-HZO adsorbent can be obtained.

[0109] Embodiment 15

[0110] The difference from Example 14 is that Lys accounts for 1.67% of the mass of AZC.

[0111] Example 16

[0112] The difference from Example 14 is that Lys accounts for 3.33% of the mass of AZC.

[0113] Embodiment 17

[0114] The difference from Example 14 is that Lys accounts for 5% of the mass of AZC.

[0115] Embodiment 18

[0116] The difference from Example 14 is that Lys accounts for 6.67% of the mass of AZC.

[0117] Embodiment 19

[0118] Fig.14 (ab) Effect of the ratio of Lys to AZC in the hybrid material on the adsorption capacity of Cr(VI) and phosphate.

[0119] Experimental conditions: Cr(VI) solution: pH=2, C0=100 mg / L, adsorbent dosage=1 g / L, t=16 h, T=25°C; phosphate solution: pH=2, C0=60 mg / L, adsorbent dosage=0.5 g / L, t=16 h, T=25°C.

[0120] It can be seen that the adsorption capacity of Cr(VI) and phosphate increases with the increase of Lys dosage. However, when the proportion of Lys in AZC reaches 6.67%, the filtration process is more difficult due to the strong hydrophilicity of the hybrid material. Therefore, the composite adsorbent prepared with Lys dosage of 5.83% of the mass of AZC was selected for subsequent experiments and recorded as Lys-HZO.

[0121] Fig.15 The infrared spectra of Lys, HZO and Lys-HZO are shown in Figure 1. As can be seen from the figure, Lys-HZO contains the characteristic functional groups of Lys and HZO, indicating that the two have been successfully hybridized.

[0122] Fig.16 The XRD diagrams of Lys, HZO and Lys-HZO are shown in Figure 2. It can be seen that Lys has a crystalline structure, while HZO and Lys-HZO have a non-crystalline structure. Therefore, it is inferred that during the hybridization process of Lys and HZO, the crystal structure is gradually destroyed, and finally it is uniformly and tightly hybridized with HZO to form an amorphous molecular-level organic-inorganic hybrid material (Lys-HZO).

[0123] Fig.17The thermogravimetric curves of Lys-HZO and HZO are shown in Figure 2. As can be seen from the figure, HZO is almost completely decomposed at around 600°C, while Lys-HZO is completely decomposed at around 700°C. This shows that the introduction of Lys enhances the thermal stability of the material.

[0124] Embodiment 20

[0125] This example investigates the effect of Lys-HZO dosage on the adsorption of Cr(VI) and phosphate.

[0126] Experimental conditions: Cr(VI) solution: adsorbent dosage = 0.5-3 g / L, C0 = 150 mg / L, pH = 2, t = 16 h, T = 25°C; phosphate solution: adsorbent dosage = 0.25-1.5 g / L, C0 = 60 mg / L, pH = 2, t = 16 h, T = 25°C.

[0127] The results are as follows Fig.18 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. It can be seen from the figure that with the increase of the dosage, the removal rate of the adsorbent for Cr(VI) and phosphate gradually increases and slowly approaches equilibrium. At the same time, the figure also shows that the unit adsorption capacity of Lys-HZO generally shows a trend of gradually decreasing with the increase of the dosage.

[0128] Embodiment 21

[0129] This example investigates the effect of the initial pH value of the solution on the adsorption of Cr(VI) and phosphate by Lys-HZO and HZO.

[0130] Experimental conditions: Cr(VI) solution: pH = 2-10, C0 = 100 mg / L, t = 16 h, T = 25 °C, adsorbent dosage = 1 g / L; phosphate solution: pH = 2-10, C0 = 60 mg / L, t = 16 h, T = 25 °C, adsorbent dosage = 0.5 g / L.

[0131] The results are as follows Fig.19 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. The adsorption of Cr(VI) and phosphate by Lys-HZO and HZO is the largest at pH = 2, and then the adsorption decreases rapidly with the increase of the pH value of the solution. However, it is obvious that the adsorption effect of Lys-HZO is greater than that of HZO in the pH range investigated, which shows that the introduction of Lys enhances the adsorption effect of the adsorbent.

[0132] Embodiment 22

[0133] This example investigates the effect of adsorption time on the adsorption of Cr(VI) and phosphate by Lys-HZO.

[0134] Experimental conditions: Cr(VI) solution: t=0-1440min, C0=100mg / L, pH=2, T=25°C, adsorbent dosage=1g / L; phosphate solution: t=0-1440min, C0=60mg / L, pH=2, T=25°C, adsorbent dosage=0.5g / L.

[0135] The results are as follows Fig. 20 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. The adsorption rate of Lys-HZO is fast in the initial stage, and then the adsorption rate begins to slow down until it reaches adsorption equilibrium. This is because in the initial stage of adsorption, there are a large number of available adsorption sites on the adsorbent surface, and there are a large number of Cr(VI) and phosphate ions in the solution, which allows Lys-HZO to adsorb quickly. However, as time goes by, the adsorption sites on the surface of the material are gradually occupied, and the Cr(VI) and phosphate in the solution gradually decrease, so the adsorption rate gradually slows down and finally reaches adsorption equilibrium.

[0136] Embodiment 23

[0137] This example investigates the adsorption capacity of Lys-HZO for different Cr(VI) and phosphate concentrations at three different temperatures (298, 308, and 318 K).

[0138] Experimental conditions: Cr(VI) solution: T = 298-318K, C0 = 75-200mg / L, pH = 2, adsorbent dosage = 1g / L, t = 24h; phosphate solution: T = 298-318K, C0 = 20-60mg / L, pH = 2, adsorbent dosage = 0.5g / L, t = 24h.

[0139] The results are as follows Fig.21 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. The adsorption capacity of Lys-HZO increases with the increase of the initial concentration of the solution and gradually approaches equilibrium. The reason may be that when the solution concentration is low, the number of adsorption sites on the adsorbent is greater than the number of Cr(VI) and phosphate ions contained in the solution. However, as the concentration of the solution increases, the adsorption sites are gradually occupied, and the adsorption eventually reaches saturation. It was also found that the adsorption capacity also increased slightly with increasing temperature, which indicates that increasing temperature is conducive to adsorption, and the process of Lys-HZO adsorbing Cr(VI) and phosphate is an endothermic reaction.

[0140] Embodiment 24

[0141] This example investigates the effect of competing ions on the adsorption of Cr(VI) and phosphate by Lys-HZO.

[0142] Experimental conditions: Cr(VI) solution: pH = 2, C0 = 100 mg / L, t = 16 h, T = 25 °C, adsorbent dosage = 1 g / L, Cl - 、SO4 2- and NO3 - =0-200mg / L; phosphate solution: pH=2, C0=60mg / L, t=16h, T=25℃, adsorbent dosage=0.5g / L, Cl - 、SO4 2- and NO3 - =0-200mg / L.

[0143] The results are as follows Fig. 22 As shown, (a) is the adsorption diagram for Cr(VI), and (b) is the adsorption diagram for phosphate. - and NO3 - In the presence of SO4 2- As the concentration of Cr(VI) and phosphate increases, the adsorption of Cr(VI) and phosphate by the adsorbent gradually decreases, causing obvious interference. However, despite this, Lys-HZO still has good anti-interference ability and has broad development prospects in the adsorption of Cr(VI) and phosphate.

Claims

1. A method for preparing an amino acid-hydrated zirconium oxide hybrid material, characterized in that The steps include: (1) dissolving the amino acid in deionized water, then dropping the ammonium zirconium carbonate solution, and then stirring at room temperature to obtain a transparent mixed solution; The amino acid, ammonium zirconium carbonate and deionized water are used in a mass ratio of 1:3.33-20:4-29; (2) drying the transparent mixed solution at a constant temperature to obtain a white solid, and then soaking, washing, and filtering the solid to obtain a white precipitate; (3) The white precipitate is dried at a constant temperature to obtain the amino acid-hydrated zirconium oxide hybrid material.

2. The method for preparing the amino acid-hydrated zirconium oxide hybrid material according to claim 1, characterized in that: The amino acid in step (1) is arginine or lysine.

3. The method for preparing the amino acid-hydrated zirconium oxide hybrid material according to claim 1, characterized in that: The stirring time in step (1) is 1 h.

4. The method for preparing the amino acid-hydrated zirconium oxide hybrid material according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 12 h.

5. The method for preparing the amino acid-hydrated zirconium oxide hybrid material according to claim 1, characterized in that: The drying temperature in step (3) is 70° C. and the drying time is 12 h.

6. Amino acid-hydrated zirconium oxide hybrid material obtained by the preparation method according to claims 1 to 5.

7. Use of the amino acid-hydrated zirconium oxide hybrid material as claimed in claim 6 in the adsorption of Cr(VI) and phosphate.

8. The use according to claim 7, characterized in that: The amino acid-hydrated zirconium oxide hybrid material has a pH value of 2-10 in the adsorption of Cr(VI) and phosphate.

9. The use according to claim 7, characterized in that: The amino acid-hydrated zirconium oxide hybrid material is added in an amount of 0.25-3 g / L in the adsorption of Cr(VI) and phosphate.

10. The use according to claim 7, characterized in that: The amino acid-hydrated zirconium oxide hybrid material has an adsorption temperature of 298-318K in the adsorption of Cr(VI) and phosphate.

Citation Information

Patent Citations

  • Method for producing metal oxide sol

    CN101031512A

  • Ozone heterogeneous oxidation solid catalyst preparation method

    CN107051476A

  • Antiperspirant compositions

    CN1323191A

  • Organic solvent-dispersed zirconia sol and its production method

    JP2007238422A

Cited By

  • Efficient phosphorus removal agent and preparation method thereof

    CN122252151A